Tempering the Reactivities of Postulated α-Oxo Gold Carbenes by Bidentate Ligands: Implication of Tricoordinated Gold Intermediates and the Development of an Expedient Bimolecular Assembly of 2,4-Disubstituted Oxazoles - Luo, Yingdong (2012)
2,4-Oxazole is an important structural motif in various natural products. An efficient modular synthesis of this structure is achieved via a [3+2] annulation between a terminal alkyne and a carboxamide by using a gold-catalyzed oxidation strategy. The postulated reactive intermediate, a terminal α-oxo gold carbene, previously known to be highly electrophilic and hence impropable to be trapped by stoichiometric external nucleophiles, is coerced to react smoothly with a carboxamide en route to the oxazole ring by a P,N- or P,S-bidentate ligand such as Mor-DalPhos; in stark contrast, often used ligands including monodentate phosphines and NHCs are totally ineffective. The role of these bidentate phosphines in this reaction is attributed to the formation of a tricoordinated gold carbene intermediate, which is less electrophilic and hence more chemoselective when reacting with nucleophiles. The success in using bidentate phosphine ligands to temper the reactivities of in-situ generated gold carbenes would likely open many new opportunities to apply the oxidative gold catalysis to the development of novel methods, and the implication of tricoordinated gold intermediates in homogeneous gold catalysis should stimulate further advance in gold catalysis.